Outlook of Diabetic Retinopathy Management through Universal Health Care in Indonesia from 2015 – 2020: Oral Presentation - Observational Study - Resident - Alfia Fatma Zaharo (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To identify the National Health Expenditure associated with diabetic retinopathy (DR) from the perspective of Jaminan Kesehatan Nasional [JKN]. Methods : A dataset of 1% of all individuals registered in JKN database was used from 2015 to 2020. We retrieved primary diagnosis with type 2 diabetes mellitus (T2DM) (ICD-10 E11) and/or T2DM with ophthalmic complications (E11.3). Further diagnosis with DR (H36) was retrieved. Four groups of medical procedures related to DR management were developed according to Indonesian Case Base Groups (INA-CBGs): diagnostic, laser photocoagulation and cryotherapy, minor (intravitreal injection), and major surgical procedures (e.g., vitrectomy). We performed descriptive analyses for the annual costs incurred for procedures, premium classifications, and regions. Results : Overall DR costs were US $41.5 million from 156,752 individuals with DR in JKN database sample. The total cost and per unit procedures cost specifically increased annually from 2015 to 2019 but declined substantially in 2020. The largest amount was spent on intravitreal injection ($36.3 million [87.5%]), whereas vitrectomy was the least ($145.0 million [0.3%]). Region 1 (Java Island) with non- beneficiaries of government subsidies (PBPU and PPU) was the major number of claims ($12.5 million [30.1%] and ($7.3 million [17.7%]), while beneficiaries of government subsidies (PBI) outside Java Island, conversely, were under average. Conclusion : There was significant increase in health expenditure associated with DR in Indonesia from 2015 to 2019, but decreased in 2020 possibly due to COVID-19 pandemic. Majority of funding was spent to treat severe spectrum of DR and concerned in urban area.